2001
DOI: 10.1056/nejm200106073442301
|View full text |Cite
|
Sign up to set email alerts
|

Nonviral Transfer of the Gene Encoding Coagulation Factor VIII in Patients with Severe Hemophilia A

Abstract: Implantation of genetically altered fibroblasts that produce factor VIII is safe and well tolerated. This form of gene therapy is feasible in patients with severe hemophilia A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
238
0
7

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(248 citation statements)
references
References 19 publications
3
238
0
7
Order By: Relevance
“…Furthermore, a method for generating FVIII expression vector modified fibroblasts from patients with hemophilia A has already been demonstrated. 35 In a previous clinical gene therapy trial, for the treatment of severe hemophilia A, skin fibroblasts were harvested from patients, transfected with a B domain deleted hFVIII expression vector, and expanded ex vivo prior to omental implantation. 35 Though the ultimate goal of that trial, a long-term increase in plasma FVIII levels, was not achieved, it did demonstrate the feasibility of generating large numbers of FVIII expressing autologous fibroblasts and the safety of infusing them back into patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a method for generating FVIII expression vector modified fibroblasts from patients with hemophilia A has already been demonstrated. 35 In a previous clinical gene therapy trial, for the treatment of severe hemophilia A, skin fibroblasts were harvested from patients, transfected with a B domain deleted hFVIII expression vector, and expanded ex vivo prior to omental implantation. 35 Though the ultimate goal of that trial, a long-term increase in plasma FVIII levels, was not achieved, it did demonstrate the feasibility of generating large numbers of FVIII expressing autologous fibroblasts and the safety of infusing them back into patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gene therapy has been explored as a promising treatment in phase 1 clinical trials. [11][12][13] However, to date, only transient, low-level FVIII protein expression has been achieved because of development of immune responses against FVIII and/or associated gene transfer vectors. In most preclinical experiments using immunocompetent hemophilia A murine and canine models, strong immune responses against FVIII after gene therapy have completely inhibited circulating FVIII activity and thus subverted the effect of gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that FVIII expression levels in CHO cells depended on the FVIII copy number on the HAC; specifically, CHO A non-viral transgene delivery method consisting of transplantation of FVIII-transduced autologous fibroblasts was tested in a clinical trial. 16 The data acquired from this phase I clinical trial showed only a modest and temporary indication of positive effects, suggesting that there is a relationship between durable transgene expression and transgene silencing. Moreover, the site of integration of a transgene into a host chromosome has a major effect on the transgene transcription rate, a phenomenon called a position effect.…”
Section: Discussionmentioning
confidence: 93%